2020
DOI: 10.1021/acs.orglett.0c00002
|View full text |Cite
|
Sign up to set email alerts
|

Intramolecular Aromatic C–H Acyloxylation Enabled by Iron Photocatalysis

Abstract: A mild and efficient protocol for the intramolecular aromatic C–H oxygenation of 2-biphenylcarboxylic acids has been achieved via iron photocatalysis. The 2-biphenylcarboxylic acids with a diverse array of substituents at both phenyl rings could furnish the oxygenation products in good to excellent yields. We speculate that the aryl carboxylate–iron­(III) complexes should generate the aroyloxy radicals and iron­(II) upon visible light irradiation.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
57
0
1

Year Published

2020
2020
2023
2023

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 91 publications
(62 citation statements)
references
References 74 publications
0
57
0
1
Order By: Relevance
“…Standard LMCT catalysis normally requires ligands to accelerate the homolysis of complexes. [10] In contrast, the present CuCl 2 -catalyzed process successfully transferred the chlorine atom to the alkene substrate without requiring exogenous ligands. Blank experiments showed that dichlorination did not proceed in the absence of light, even with heating (Supporting Information, Table S1, entries 17 and 18).…”
mentioning
confidence: 81%
See 1 more Smart Citation
“…Standard LMCT catalysis normally requires ligands to accelerate the homolysis of complexes. [10] In contrast, the present CuCl 2 -catalyzed process successfully transferred the chlorine atom to the alkene substrate without requiring exogenous ligands. Blank experiments showed that dichlorination did not proceed in the absence of light, even with heating (Supporting Information, Table S1, entries 17 and 18).…”
mentioning
confidence: 81%
“…In sharp contrast, the use of ligand-to-metal charge transfer (LMCT) is underdeveloped and only a few examples of the application of this process in synthetic chemistry have been reported in recent years. [10] In nature, chlorine typically exists in the form of inorganic chloride salts, and so it would be ideal to use Earth-abundant chloride salts as chlorine sources under photocatalytic conditions. However, this remains a formidable challenge given the fact that the oxidation potential of the chloride anion is much higher than the oxidation potentials of common photocatalysts.…”
mentioning
confidence: 99%
“…Moreover, the UV/Vis spectra indicated that the solution of 1:1 iron and ligand exhibited a significant optical absorption in the visible range, compared with no absorption of visible light for either the iron salt or ligand individually. Very recently, they further extended this iron photocatalysis strategy to the intramolecular aromatic C−H oxygenation of 2‐biphenylcarboxylic acids (Scheme 12 c), which provided a facile and sustainable way to generate important benzo‐3,4‐coumarins in good to excellent yields [26b] …”
Section: Light‐induced Iron Photoredox Catalysismentioning
confidence: 99%
“…Ligand-to-metal charge transfer (LMCT) processes have been employed to generate reactive open-shell intermediates from coordination complexes upon light irradiation. [21][22][23][24][25][26][27] Notably, aliphatic copper(II)-carboxylate complexes can undergo LMCT upon irradiation through innersphere electron transfer from a carboxylate ligand to copper(II), forming a dissociated carboxyl radical and copper(I). We envisioned that this photochemical process could serve as a key design principle in the development of a general light-and copper-enabled decarboxylative functionalization platform for aromatic carboxylic acids.…”
mentioning
confidence: 99%